water treatment options for dissolved cyanotoxins - NEWCOMBE, Gayle; NICHOLSON, Brenton (Journal of water supply : research and technology - AQUA, 2004)
When treating water subject to a cyanobacterial bloom the first priority should be removal of intact cells using separation techniques such as coagulation or membrane filtration. Chlorination and ozonation are effective for the destruction of residual dissolved microcystins and cylindrospermopsin. Anatoxin-a can be effectively removed using ozone, although chlorine is relatively ineffective. Oxidation techniques do not appear to be the best method for the treatment of saxitoxins under normal treatment plant operating conditions. Powdered activated carbon can be effective for the removal of all toxins, except, perhaps, microcystin LA, provided the appropriate carbon and the correct dose is applied. Granular activated carbon filters show a limited lifetime for the adsorption of most microcontaminants, including cyanotoxins. The biodegradation of cyanotoxins across GAC filters shows great potential as a treatment process.